Understanding the Social and Emotional Wellbeing of Aboriginal LGBTIQ(SB)+ Youth in Victoria’s Youth Detention - Phelan, Péta; Oxley, Robyn (Social Inclusion, 2021)
Aboriginal youth are overrepresented within Victoria’s criminal justice system (Cunneen, 2020). Aboriginal and Torres Strait Islander youth are diverse people with diverse needs: It is imperative to understand what those needs are and how they can be supported within Victoria’s youth justice centres. Research has identified that Aboriginal youth in Victoria’s justice system have higher rates of psychopathology (Shepherd et al., 2018), higher rates of recidivism (Cunneen, 2008), higher pre-custody rates and post-release rates of substance abuse (Joudo, 2008) and lower rates of rehabilitation (Thompson et al., 2014) than non-Indigenous counterparts. It is critical to explore how the Victorian youth justice system identifies and implements the provision of services that consider lesbian, gay, bisexual, transgender, intersex, queer, sistergirl and brotherboy (LGBTIQSB+) identities of Aboriginal youth in custody. This is because additional levels of systemic disadvantage, discrimination, stigma, and social exclusion that impact LGBTIQ+ youth specifically (Cunneen, Goldson, & Russell, 2016) as well as Aboriginal identity, further compound and jeopardize the social and emotional wellbeing of those embodying intersectional identities. This article will examine the services available to Aboriginal LGBTIQSB+ youth in the Victorian criminal justice system. Aboriginal, Torres Strait Islander, Indigenous and First Nations People will be used interchangeably throughout this document.